2019
DOI: 10.1038/s41598-019-48705-0
|View full text |Cite
|
Sign up to set email alerts
|

Differentiating cervical metastatic lymphadenopathy and lymphoma by shear wave elastography

Abstract: Shear wave elastography (SWE) is a recent technological advance of ultrasonography (US) to assess tissue stiffness. The purpose of this study is to assess tissue stiffness of malignant cervical lymph nodes (LN) with SWE, to reveal diagnostic performance of SWE in differentiating metastatic LN from lymphoma, and to assess inter-observer agreement of SWE. We assessed 62 malignant LN (24 lymphomas and 38 metastatic LN) and their median speed was 6.34 m/s and median elasticity was 69.7 kPa. Add of SWE with convent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
11
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 27 publications
5
11
1
Order By: Relevance
“…Despite including various pathologies, we found, as already published by several groups, that malignant LNs were significantly stiffer than benign ones and, additionally, we found that lymphomas showed stiffness values intermediate between benign LNs and carcinomas. Our results are similar to those obtained by Zhang et al (Zhang et al, 2017) using a point SWE system and Chae using Toshiba SWE (Chae et al, 2019).…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…Despite including various pathologies, we found, as already published by several groups, that malignant LNs were significantly stiffer than benign ones and, additionally, we found that lymphomas showed stiffness values intermediate between benign LNs and carcinomas. Our results are similar to those obtained by Zhang et al (Zhang et al, 2017) using a point SWE system and Chae using Toshiba SWE (Chae et al, 2019).…”
Section: Discussionsupporting
confidence: 92%
“…Our "nodular pattern" that was found to be related to malignancy could be similar to the "markedly heterogeneous with some unfilled regions" pattern described by Bhatia et al (Bhatia et al, 2016), the "heterogeneous pattern" described by Luo for metastatic disease in breast cancer (Luo et al, 2019), or the "large red area" and "almost red" patterns described by Chae (Chae et al, 2019). The "rim pattern" that was also suggestive of malignancy has been reported in primary breast cancer.…”
Section: Discussionsupporting
confidence: 86%
See 3 more Smart Citations